Telemedicine acceptance during the COVID-19 pandemic: User satisfaction and strategic healthcare marketing considerations. Issue 2 (3rd July 2021) - Sabbir, Md. Mahiuddin; Taufique, Khan Md Raziuddin; Nomi, Marzia
Abstract: A lot remains unexplored regarding the antecedents and outcomes of telemedicine acceptance from health service marketing perspective. This study addresses this gap by integrating the Health Belief Model and the Unified Theory of Acceptance and Use of Technology model in the context of generation Y and Z's response to the COVID-19 pandemic. Data collected from 293 respondents were analyzed using structural equation modeling. The results confirm theoretical rigor of integrating two models examining the antecedents and user satisfaction as an outcome of telemedicine acceptance. The findings also suggest marketing strategies for implementing telemedicine during pandemic. Future research directions are highlighted.